2017
DOI: 10.1051/0004-6361/201630346
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and rotational properties of near-Earth asteroid (162173) Ryugu, target of the Hayabusa2 sample return mission

Abstract: Context. The JAXA Hayabusa2 mission will perform the first ever sample return from a primitive asteroid. The target near-Earth asteroid (162173) Ryugu will be reached in mid-2018 and its samples will be returned to the Earth by the end of 2020. Aims. We want to improve the current knowledge of the compositional and rotational properties of Ryugu, which are still presenting some uncertainties that might affect the mission operations and scientific return. Methods. We acquired high-quality photometric time-serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 22 publications
4
36
1
Order By: Relevance
“…Ground-based observations of asteroid Ryugu indicated that its surface materials would possibly consist of unheated CM chondrite (Vilas 2008) based on an observation of the 0.7-μm band, or heated carbonaceous chondrite because its Vis-NIR spectrum corresponds with the spectrum of Murchison CM2 chondrite heated at 550-900 °C. Their spectral slopes around 0.7 μm are very similar to each other (Sugita et al 2013;Perna et al 2017).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Ground-based observations of asteroid Ryugu indicated that its surface materials would possibly consist of unheated CM chondrite (Vilas 2008) based on an observation of the 0.7-μm band, or heated carbonaceous chondrite because its Vis-NIR spectrum corresponds with the spectrum of Murchison CM2 chondrite heated at 550-900 °C. Their spectral slopes around 0.7 μm are very similar to each other (Sugita et al 2013;Perna et al 2017).…”
Section: Introductionsupporting
confidence: 61%
“…We can conclude that NIRS3 has sufficient ability to evaluate the surface property of the CM-chondrite-like target asteroid because it has sensitivity for the wide range of wavelength up to 3.2 μm. In the previous observations, spectral heterogeneity of Ryugu was reported; Vilas (2008) suggested that a 0.7-μm absorption band exists; on the other hand, spectra recorded by Bus and Binzel (2002), Lazzaro et al (2013), Sugita et al (2013), and Perna et al (2017) showed no such absorption. The results may indicate that either the surface of Ryugu is extremely heterogeneous or a short-lived resurfacing event excavated hydrous minerals showing the 0.7-μm absorption band.…”
Section: Discussionmentioning
confidence: 92%
“…), near‐IR slope (Perna et al. ; Le Corre et al. ) and the intensity of the absorption at 0.7 μm (Vilas ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of suitable meteorite analogs for Ryugu suggest that unusual or heated CM and CI carbonaceous chondrites may be best‐fitting to the asteroid's spectral characteristics (Perna et al. ; Kitazato et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation